2014
DOI: 10.1155/2014/814057
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Bone Forming Cells in Bone Diseases and Anabolic Effects of Strontium-Containing Agents and Biomaterials

Abstract: Age-related bone loss and osteoporosis are associated with bone remodeling changes that are featured with decreased trabecular and periosteal bone formation relative to bone resorption. Current anticatabolic therapies focusing on the inhibition of bone resorption may not be sufficient in the prevention or reversal of age-related bone deterioration and there is a big need in promoting osteoblastogenesis and bone formation. Enhanced understanding of the network formed by key signaling pathways and molecules regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 116 publications
(132 reference statements)
1
28
0
2
Order By: Relevance
“…Although the precise mechanism of the role of Sr concentration on osteogenesis and bone turnover is not fully understood, the increased bone formation and its suppressed turnover, within the specified implant period, suggests that Sr is dose dependently taken up and distributed by the osteoblasts in newly formed bone tissue. The Sr ions released from the degrading implant possibly affects the osteocytes, which in turn controls the activity of osteoblasts and osteoclasts (Tan et al 2014). The mechanical pressure applied by the newly forming bone matrix is sensed by osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of the role of Sr concentration on osteogenesis and bone turnover is not fully understood, the increased bone formation and its suppressed turnover, within the specified implant period, suggests that Sr is dose dependently taken up and distributed by the osteoblasts in newly formed bone tissue. The Sr ions released from the degrading implant possibly affects the osteocytes, which in turn controls the activity of osteoblasts and osteoclasts (Tan et al 2014). The mechanical pressure applied by the newly forming bone matrix is sensed by osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Strontium acts on bone cells to control bone resorption and regulate genes involved in osteoblastic cell replication, differentiation and survival. More specifically, it inhibits osteoclasts and therefore bone resorption, and improves the differentiation and activity of osteoblasts [182][183][184][185][186][187][188] . Li et al investigated the effects of 10% Sr substituted HA coatings on implant fixation in a rat model, and found that after 12 weeks, bone to implant contact increased by 49.9%…”
Section: Refractory Ion Containing Coatingsmentioning
confidence: 99%
“…In addition, inhibition of TGF-β action by SB431542 antagonized anti-apoptotic effects of pitavastatin, indicates the suppressive effect of pitavastatin on osteoblast apoptosis through TGFβ/Smad3 signaling pathway [81]. SB431542 is an inhibitor of TGFβ signaling pathways but has no effect on BMPs, so the TGFβ/Smad3 signaling pathway has no relationship with BMPs [19].…”
Section: Statins Inhibit Osteoblastic Apoptosis By Tgfβ/smad3 Signalimentioning
confidence: 99%